The Place and History of the Activities of Kazakhstan in the United Nations Organization (1991 – 2016) - KARASAYEV, Gani M.; ZHAXYGELDINOV, Zhandos N.; YENSENOV, Kanat A.; NAIMANBAYEV, Bekmurat R.; BAKIROVA, Zhanat S. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
This research article considers the activities of the United Nations Organization, international relations, safety and reconciliation of the world states. Moreover, the paper informs about the First President of Kazakhstan N.A. Nazarbayev’s speeches at international UNO conferences of international importance, his world and global initiatives, including the decision to non-proliferation of nuclear weapons that has been supported throughout the world. Obviously, these initiatives have been supported by Secretary General UN Ban Ki – moon and others and have been concluded as one of the most important events and historical missions in modern history. The membership of Kazakhstan in the United Nations, its involvement in solving global problems, views and proposals of Kazakhstan on keeping peace and harmony among the world's nations have been well-recognized throughout the world. Kazakhstan connecting Europe and Asia on the transit route as a Eurasian country is situated geopolitically convenient. It occupies the 9th place on the world map. The population of the country is 18 million. The First President of Kazakhstan N.A. Nazarbayev is a globally recognized politician. Its recommendations and initiatives have been recognized worldwide. Therefore, it is obvious that the history of international relations and the activities of international organizations should be studied from historical view.